Creating a Culture of Security in the University of Maryland Libraries - Lowry, Charles B; Goetsch, Lori A. (My University, 2001)
A critical part of building a shared culture of mutual responsibility for security and safety is a thorough understanding of all the elements of a library’s security environment. To address the need for a more coherent approach to library safety and security that reinforces a philosophy of shared responsibility among all staff, the University of Maryland Libraries embarked upon an assessment of policies, procedures, and facilities in partnership with the Association of Research Libraries. Begun in the fall of 1997, the security study and subsequent development of practice and policy were implemented over a two-year period and serve as a model comprehensive approach for a large academic library system.
Citation: Lowry, Charles B. and Lori A. Goetsch, “Creating a Culture of Security in the University of Maryland Libraries,” portal: Libraries and the Academy, 1(4):455-464, October 2001.